Statistical Analyses of Frosts in Iran - Hosein Asakereh; Soheila Rahimi; Fatemeh Tarkarani (مخاطرات محیط طبیعی, 2012)
The temperature phases could determine its effects on the environment. One of the important temperature phases that could be a disaster is frost. Frost has important roles on Biological activity as well as on economical. In current paper in order to analyze frost in Iran, we used database of minimum temperature of Iran. This data based is arranged for 43 years (15992 days) and 15 ×15 KM resolution (7187 pixels for all over Iran). So the database has 15992×7187 dimensions. All the operating calculations have performed on this matrix. As in classical documents zero degrees Celsius have been chosen as threshold for frost in the database. The analyses have been taking place on the temperature equal or below of this threshold. It has been done by using softwares such as Surfer and MATLAB. Time series analyses of frost shows those 9224 days out of 15992 days have experienced the frozen day. There are a strong oscillatory behavior and weak, not statistical significant trends in frost temperature time series as well as a jump in its middle. Oman Sea cost as well as Persian Gulf shores never have experienced the frost days. The height lands and high latitudes area has most experiences in freezing days as well as in extensive. The average of maximum days with frost was 145 days.